Membangun Peran Orang Tua melalui Kegiatan Menggambar dan Berkarya Untuk Anak Usia Dini di TK Negeri 31 Simpang Sungai Duren - Shoheri, Abim; Ardana, Nabilla Olivia; Setiawati, Nursela; Zai, Dekristiani; Amanda, Naya Yurika; Utami, Winda Sherly; Indriyani (Irajagaddhita, 2026)
This community service program aims to strengthen parental involvement in early childhood education through drawing and creative activities at TK Negeri 31 Simpang Sungai Duren. The background of this activity emphasizes the importance of parents’ presence and participation in accompanying children during the learning process at school. Using a participatory approach, the activity was carried out through the stages of preparation, implementation, and evaluation. In the implementation stage, children drew pictures of their parents or family members and created photo frames using ice cream sticks with the assistance of their parents. The activity was attended by 20 children and 20 parents and was conducted on November 21, 2025. The results of the activity showed that parents were actively involved, provided positive support, and established good interaction throughout the process. The children appeared enthusiastic, creative, and initiative in completing their work, while the collaboration strengthened communication and emotional bonding between parents and children. Overall, this program succeeded in increasing parental participation and creating a meaningful learning experience through enjoyable and collaborative art activities.